Locomotion characteristics and match-induced impairments in physical performance in male elite team handball players - Michalsik, L. B.; Aagaard, P.; Madsen, K. (International Journal of Sports Medicine, 2013)
The purpose of this study was to determine the physical demands and match-induced impairments in physical performance in male elite Team Handball (TH) players in relation to playing position. Male elite TH ? eld players were closely observed during 6 competitive seasons. Each player (wing players: WP, pivots: PV, backcourt players: BP) was evaluated during match-play using video recording and subsequently performing locomotion match analysis. A total distance of 3 627 ± 568 m (group means ± SD) was covered per match with a total effective playing time (TPT) of 53:51 ± 5:52 min:s, while full-time players covered 3 945 ± 538 m. The mean speed was 6.40 ± 1.01 km · h - 1 . High-intensity running constituted only 1.7 ± 0.9 % of TPT per match corresponding to 7.9 ± 4.9 % of the total distance covered. An average of 1 482.4 ± 312.6 activity changes per player (n = 82) with 53.2 ± 14.1 highintensity runs were observed per match. Total distance covered was greater in BP (3 765 ± 532 m) and WP (3 641 ± 501 m) than PV (3 295 ± 495 m) (p < 0.05), and WP performed more high-intensity running (10.9 ± 5.7 % of total distance covered) than PV (8.5 ± 4.3 %, p < 0.05) and BP (6.2 ± 3.2 %, p < 0.01). The amount of high-intensity running was lower (p < 0.05) in the second (130.4 ± 38.4 m) than in the ? rst half (155.3 ± 47.6 m) corresponding to a decrease of 16.2 %. In conclusion, modern male elite TH is a complex team sport that comprises several types of movement categories, which during match-play place moderate-to-high demands on intermittent endurance running capacity and where the amount of high-intensity running may be high during brief periods of the match. Signs of fatigue-related changes were observed in terms of temporary impaired physical performance, since the amount of high-intensity running was reduced in the second half. Notably, physical demands di? ered between playing positions, with WP demonstrating a more intensive activity pattern than BP and PV, respectively.